Cfd Simulation To Study The Effects Of Ribs In A Converging Nozzle Flow At Sonic Mach Number - Khan, Ambareen (2020)
The presence of a blunt base leads to flow separation in aerodynamic bodies, which causes a low-pressure in the wake region. At sonic Mach number, low pressure in the wake region contributes up to sixty percent of the total drag. This study is conducted to study the effect of the rectangular ribs on the base pressure. The parameters considered are the nozzle pressure ratio, rib’s aspect ratio, Length to Diameter (L/D) ratio of the duct when placed circumferentially operating from subsonic to sonic Mach number. The simulation is performed using CFD, and the k-ɛ turbulence model is employed. Initially, the simulation results obtained are validated with experimental work for different L/D ratio of the duct at various Nozzle Pressure Ratio’s (NPR), and the aspect ratio of the ribs from 3:1 to 3:3 for area ratio of 6.25. The results are in good agreement with the experimental results. Later simulations are done for a single rib, which is placed at different locations and aspect ratios for NPRs in the range from 1.5 to 5 from the base. Base pressure variations, velocity, and pressure field changes for the above variables are discussed. The simulation results indicate that the rib breaks the primary vortex at the base and form multiple vortices and hence controls the base pressure in the wake region. The results show that a rectangular rib with a lower aspect ratio is effective in reducing the base pressure, whereas the rib with a higher aspect ratio tends to increase the base pressure. The simulations are also conducted for a duct with a diameter, D = 20 mm. In this case, the rectangular rib with aspect ratios 3:1, 3:2, and 3:3 is placed at 20 mm, 40 mm, 60 mm, and 80 mm locations, for the same NPRs. Results show that the height and position of the rib plays a vital role in controlling the base pressure.